1999
DOI: 10.1002/(sici)1098-2795(199907)53:3<318::aid-mrd7>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the first cleavage post‐insemination affects cryosurvival of in vitro–produced bovine blastocysts

Abstract: The time of the first cleavage of bovine zygotes during in vitro culture can affect the rate of development and cell number of the blastocysts. The aim of this work was to study the effect of the timing of first cleavage on the cryosurvival of the resulting blastocysts. Following standard IVM and IVF, zygotes were cultured in modified synthetic oviduct fluid (SOF), with 10% fetal calf serum (FCS) added 48 hr post insemination, in a humidified atmosphere of 5% CO 2, 5% O 2 and 90% N 2. Embryos which cleaved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
3
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 39 publications
6
28
3
2
Order By: Relevance
“…Obtained results are in agreement with data shown in literature (Han et al, 1994;Hasler et al, 1997;Dinnyes et al, 1999;Rios et al, 2010), as it is generally expected for morphologically normal and more developmentally advanced embryos on the given day to be of higher quality and have higher viability after cryopreservation. It was also shown that day 7 blastocysts and expanded blastocysts survived cryopreservation better than their slower developing day 8 and 9 counterparts (Han et al, 1994;Saha et al, 1996;Dinnyes et al, 1999;Gomez et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Obtained results are in agreement with data shown in literature (Han et al, 1994;Hasler et al, 1997;Dinnyes et al, 1999;Rios et al, 2010), as it is generally expected for morphologically normal and more developmentally advanced embryos on the given day to be of higher quality and have higher viability after cryopreservation. It was also shown that day 7 blastocysts and expanded blastocysts survived cryopreservation better than their slower developing day 8 and 9 counterparts (Han et al, 1994;Saha et al, 1996;Dinnyes et al, 1999;Gomez et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Fast cleaving bovine embryos have an altered gene expression (Lonergan et al 2000, Ward et al 2001, Gutiérrez-Adán et al 2004, Dode et al 2006 or altered polyadenylation status of several developmentally important gene transcripts (Pocar et al 2001, Brevini-Gandolfi et al 2002 and a higher chance of reaching advanced developmental stages in comparison with late cleaving embryos (Van Soom et al 1992, Dinnyés et al 1999, Lequarré et al 2003, Favetta et al 2004, Gutiérrez-Adán et al 2004. Studies investigating the effect of developmental kinetics on the incidence of apoptosis during preimplantation embryo development in bovine are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…1). The time points and criteria for the selection of fast or slow developing embryos were determined on the basis of previous studies in similar culture conditions (Dinnyés et al 1999, Yoshioka et al 2000, Lequarré et al 2003 and verified in a preliminary experiment (data not shown).…”
Section: Experimental Designmentioning
confidence: 99%
“…Incidence of delayed cleavage and overall lower cleavage rate in vitrified-warmed oocytes after IVF were also reported in sheep [16]. Higher potential of oocytes cleaving earlier, compared to those cleaving later, to reach blastocysts [24,25], to survive cryopreservation [26] and to achieve pregnancy [24] have been reported in cattle. Although genetic factor [30], bull individuals for sperm [25], chromosomal normality [31], embryonic sex [24,31,32], and culture conditions [33] are involved in the developmental kinetics of embryos, the principle factor that controls the timing of first cleavage remains unclear.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, the oocytes use their own MTOC dispersed in the cytoplasm for aster formation; that is called cytoplasmic aster [22,23]. Timing of first cleavage in IVF-derived bovine oocytes is important for yield and quality of blastocysts, as oocytes cleaving earlier are more likely to become blastocysts [24,25], and the resulting blastocysts have higher cryosurvival potential [26] and higher pregnancy rates [24] than those cleaving later. Thus, developmental kinetics can be used as a proxy of embryo quality.…”
Section: Introductionmentioning
confidence: 99%